2017
DOI: 10.5194/acp-17-14199-2017
|View full text |Cite
|
Sign up to set email alerts
|

Dry versus wet marine particle optical properties: RH dependence of depolarization ratio, backscatter, and extinction from multiwavelength lidar measurements during SALTRACE

Abstract: Triple-wavelength lidar observations of the depolarization ratio and the backscatter coefficient of marine aerosol as a function of relative humidity (RH) are presented with a 5 min time resolution. The measurements were performed at Barbados (13 • N, 59 • W) during the Saharan Aerosol Long-range Transport and Aerosol-Cloud interaction Experiment (SALTRACE) winter campaign in February 2014. The phase transition from spherical sea salt particles to cubic-like sea salt crystals was observed with a polarization l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
138
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(174 citation statements)
references
References 79 publications
26
138
4
Order By: Relevance
“…This spectral dependency has also been reported in Kotchenruther et al (1999) for in situ measurements at 450, 550, and 700 nm, obtaining increasing enhancement factors with wavelength, and in Zieger et al (2013), where the same behavior is observed for marine aerosols. As is reported in Haarig et al (2017), the enhancement factor dependency with wavelength suggests that larger wavelengths have an enhancement factor larger than short ones, which in fact was also evidenced in this work.…”
Section: F λ β (Rh) Measured and Retrieved By Combining In Situ Data supporting
confidence: 72%
See 2 more Smart Citations
“…This spectral dependency has also been reported in Kotchenruther et al (1999) for in situ measurements at 450, 550, and 700 nm, obtaining increasing enhancement factors with wavelength, and in Zieger et al (2013), where the same behavior is observed for marine aerosols. As is reported in Haarig et al (2017), the enhancement factor dependency with wavelength suggests that larger wavelengths have an enhancement factor larger than short ones, which in fact was also evidenced in this work.…”
Section: F λ β (Rh) Measured and Retrieved By Combining In Situ Data supporting
confidence: 72%
“…A decrease in AE 355−532 nm (∼ 0.4 km −1 ) means an increase in the predominance of larger particles, and a decrease in the PLDR 532 nm (∼ 0.13 km −1 ) is related to particles becoming more spherical. This correlation between AE 355−532 and PLDR has been observed in previous studies associated with hygroscopic growth (Granados-Muñoz et al, 2015;Haarig et al, 2017).…”
Section: Hygroscopic Study During Slope I 421 Conditions For Hygrossupporting
confidence: 54%
See 1 more Smart Citation
“…During PS98 at 5 • S, 2500 km from the African coast, the lidar ratio between 1.5 and 2.4 km is around 35 sr, which is considerably lower than the characteristic values of pure dust (S 532 ≈ 55 sr; Tesche et al, 2011a). This may result from marine aerosol transported upward by turbulent mixing processes (Haarig et al, 2017).…”
Section: Time Seriesmentioning
confidence: 88%
“…Murayama et al (1999) measured high depolarisation ratios (≈ 10 %) at 532 nm in the lower atmosphere associated with sea breeze events in the coastal area of Tokyo Bay. During the Saharan Aerosol Long-range Transport and Aerosol-CloudInteraction Experiment (SALTRACE) winter campaign 2014 at Barbados, Haarig et al (2017) detected an increase of the particle depolarisation ratio up to 12 % at 355 nm, 15 % at 532 nm, and 10 % at 1064 nm when the RH drops below 50 %. Sakai et al (2000) observed low depolarisation ratios (< 5 %) at 532 nm over a wide range of relative humidities, whereas δ par > 10 % was measured at low RH (< 50 %) in air masses which had passed over the Pacific Ocean.…”
Section: Ps95 -Marine Aerosol Conditionsmentioning
confidence: 99%